Antimicrobial Effects of Equine Platelet Lysate - Gordon, Julie; Álvarez-Narváez, Sonsiray; Peroni, John F. (Frontiers in Veterinary Science, 2021)
The development of antimicrobial resistant bacteria and the lack of novel antibiotic strategies to combat those bacteria has prompted this study designed to evaluate platelet lysate (PL) as a biological alternative antimicrobial product. Platelet lysate is an acellular platelet-derived product rich in growth factors and cytokines that is manufactured via plateletpheresis and pooled from donor horses. In the current study, we sought to define the antimicrobial properties of PL on select gram-positive and gram-negative bacteria. Results from an end-point in vitro assay showed that PL did not support bacterial growth, and in fact significantly reduced bacterial content compared to normal growth media. An in vitro assay was then utilized to further determine the effects on bacterial growth dynamics and showed that all strains exhibited a slower growth rate and lower yield in the presence of PL. The specific effects of PL were unique for each bacterial strain: E. coli and P. aeruginosa growth was affected in a concentration-dependent manner, such that higher amounts of PL had a greater effect, while this was not true for S. aureus or E. faecalis. Furthermore, the onset of exponential growth was delayed for E. coli and P. aeruginosa in the presence of PL, which has significant clinical implications for developing a dosing schedule. In conclusion, our findings demonstrate the potential value of PL as a broad-spectrum antimicrobial that would offer an alternative to traditional antibiotics for the treatment of bacterial infection in equine species.